Here we go again eaudiobook A novel. - Cochrun, Alison (Simon & Schuster Audio, 2024)
One of Elle 's Best Romance Novels of 2024 A Publishers Weekly and Book Riot Best Romance of 2024 The author of the "sexy, insightful, and utterly charming" ( BuzzFeed ) Kiss Her Once for Me returns with a new queer rom-com following once childhood best friends forced together to drive their former teacher across the country. A long time ago, Logan Maletis and Rosemary Hale used to be friends. They spent their childhood summers running through the woods, rebelling against their conservative small town, and dreaming of escaping. But then an incident the summer before high school turned them into bitter rivals. After graduation, they went ten years without speaking. Now in their thirties, Logan and Rosemary find they aren't quite living the lives of adventure they imagined for themselves. Still in their small town and working as teachers at their alma mater, they're both stuck in old patterns. Uptight Rosemary chooses security and stability over all else, working constantly, and her most stable relationship is with her label maker. Chaotic and impulsive Logan has a long list of misguided ex-lovers and an apathetic shrug she uses to protect herself from anything real. And as hard as they try to avoid each other—and their complicated past—they keep crashing into each other. Including with their cars. But when their beloved former English teacher and lifelong mentor tells them he has only a few months to live, they're forced together once and for all to fulfill his last wish: a cross-country road trip. Stuffed into the gayest van west of the Mississippi, the three embark on a life-changing summer trip—from Washington state to the Grand Canyon, from the Gulf Coast to coastal Maine—that will chart a new future and perhaps lead them back to one another.